2008
DOI: 10.1007/s11270-008-9791-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Removal in Pilot-Scale Constructed Wetlands Treating Eutrophic River Water: Assessment of Plants, Intermittent Artificial Aeration and Polyhedron Hollow Polypropylene Balls

Abstract: Seven experimental pilot-scale subsurface vertical-flow constructed wetlands were designed to assess the effect of plants [Typha latifolia L. (cattail)], intermittent artificial aeration and the use of polyhedron hollow polypropylene balls (PHPB) as part of the wetland substrate on nutrient removal from eutrophic Jinhe River water in Tianjin, China. During the entire running period, observations indicated that plants played a negligible role in chemical oxygen demand (COD) removal but significantly enhanced am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 43 publications
2
34
0
2
Order By: Relevance
“…Nevertheless, intermittent operation with a HLR of 0.12 m 3 /m 2 d could result in filter clogging while higher HLR could lead to system breakdown quickly (Leuerenz et al, 2009;Li et al, 2015). As an option, intermittent artificial aeration in wetlands matrix could achieve the alternation of aerobic and anaerobic environment, and create conditions for improved nutrient removal (Boog et al, 2014;Fan et al, 2013;Foladori et al, 2013;Li et al, 2014;Tang et al, 2009). A few studies also showed that intermittent artificial aeration enhanced pollutant removal efficiency in multi-soil-layering (MSL) system, and in soil infiltration bioreactor incorporated with pyrite-based (mixotrophic) denitrification with surface loading rate of 0.106 m 3 /m 2 d and SWIS with HLR of 0.06 m 3 /m 2 d (Kong et al, 2015;Luanmanee et al, 2002;Pan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, intermittent operation with a HLR of 0.12 m 3 /m 2 d could result in filter clogging while higher HLR could lead to system breakdown quickly (Leuerenz et al, 2009;Li et al, 2015). As an option, intermittent artificial aeration in wetlands matrix could achieve the alternation of aerobic and anaerobic environment, and create conditions for improved nutrient removal (Boog et al, 2014;Fan et al, 2013;Foladori et al, 2013;Li et al, 2014;Tang et al, 2009). A few studies also showed that intermittent artificial aeration enhanced pollutant removal efficiency in multi-soil-layering (MSL) system, and in soil infiltration bioreactor incorporated with pyrite-based (mixotrophic) denitrification with surface loading rate of 0.106 m 3 /m 2 d and SWIS with HLR of 0.06 m 3 /m 2 d (Kong et al, 2015;Luanmanee et al, 2002;Pan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CWs performances are frequently reported to be satisfactory (over 80%) for suspended solids (SS) and organic matter [6]; however, for nutrient removal, high variations in removal rates are often observed. Previous studies reported that total nitrogen (TN) and total phosphorus (TP) removal efficiencies are reported to be varied between 40%-55% and 40%-60%, respectively, in different CWs [6][7][8], suggesting the need to improve nutrient removal in order to obtain more reliable treatment performances.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of dissolved oxygen (DO) in wastewater limits this microbial process [13]. Although nitrification can occur at low DO levels, the reaction rate is considerably less when DO levels fall below 2 mg/L [6]. Plants in CWs can supply oxygen in the rhizospheres and enhance nitrification processes [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of subsurface flow CWs or floating systems to treat eutrophic water has also been reported by several authors (Sheng Bing et al, 2007; Tang et al, 2009; Li et al, 2008. Li et al ( 2008 ) compared the efficiencies of different types of CWs, including FWSCWs, horizontal subsurface flow CWs (HFCWs) and vertical subsurface flow CWs (VFCWs).…”
Section: Aq2mentioning
confidence: 86%